2019
DOI: 10.3390/membranes9080097
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Submerged Forward Osmosis for Water Recovery and Pre-Concentration of Wastewater before Anaerobic Digestion: A Pilot Scale Study

Abstract: Applying forward osmosis directly on raw municipal wastewater is of high interest for the simultaneous production of a high quality permeate for water reuse and pre-concentrating wastewater for anaerobic digestion. This pilot scale study investigates, for the first time, the feasibility of concentrating real raw municipal wastewater using a submerged plate and frame forward osmosis module (0.34 m2) to reach 70% water recovery. Membrane performance, fouling behavior, and effective concentration of wastewater co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The resultant by-products may become more severe threats to both organisms and environment as possess higher stability and probably more poisonous. Currently, the A pilot scale submerged plate and frame FO module has been applied for the pre-concentration of real raw municipal wastewater prior to anaerobic digestion [119]. The pure water flux of 15 L m −2 h −1 was obtained with NaCl as feed and draw solution, respectively.…”
Section: Contaminants Of Emerging Concerns Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant by-products may become more severe threats to both organisms and environment as possess higher stability and probably more poisonous. Currently, the A pilot scale submerged plate and frame FO module has been applied for the pre-concentration of real raw municipal wastewater prior to anaerobic digestion [119]. The pure water flux of 15 L m −2 h −1 was obtained with NaCl as feed and draw solution, respectively.…”
Section: Contaminants Of Emerging Concerns Removalmentioning
confidence: 99%
“…It was found that after four concentration cycles, the surface grafted PAMAM dendrimer was capable of sustaining the high NH4 + -N, the improved antifouling capacity allowed effective restoration the NH4 + -N retention rate to approximately its initial value, after a simple physical cleaning. A pilot scale submerged plate and frame FO module has been applied for the pre-concentration of real raw municipal wastewater prior to anaerobic digestion [119]. The pure water flux of 15 L m −2 h −1 was obtained with NaCl as feed and draw solution, respectively.…”
mentioning
confidence: 99%
“…Ansari et al demonstrated the feasibility to concentrate, by 10-fold, WW, and to reach a 1000 mg·L −1 COD concentration, which is suitable for downstream anaerobic digestion [ 127 ]. Moving to a pilot scale, water concentration factors (WCF) of 5 and 2.5 were achieved with a spiral wound membrane and submerged plate and frame (P&F) TFC modules, respectively [ 128 , 129 ]. One of the limitations of raw WW concentration is the incomplete and heterogeneous recovery of nutrients (N, P, COD).…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…However, initial experiments using FO on primary treated (screened) WW demonstrated that the accumulated fouling layer was loose and easily reversible [ 111 ]. Additionally, the concentration of raw sewage using the submerged FO system proved to be promising with operation without clogging and no major fouling issue [ 128 ]. Another limitation of FO process concentration can be the toxicity of some compounds for downstream treatments—i.e., anaerobic digestion inhibitors, such as SO 4 2− , NH 3 , and salts.…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
See 1 more Smart Citation